FAFIDAM : o conservadorismo da Igreja nas práticas educativas no contexto do estado ditador - Maria Lenúcia de Moura (2016)
The Faculty of Philosophy Dom Aureliano Matos, institution of higher education located in the micro-region of Baixo Jaguaribe, was established in one of the most dramatic periods in Brazilian history: the recent civil-military dictatorship. Its creation was part of a project conducted by the Diocese of Fortaleza, led by bishop Aureliano Matos next to Limoeirense elite. In order to understand the impacts that college produced by the Limoeirense society at that point, we analyze not only the local and specific context of the dictatorship, as well as the policy framework implemented for the education sector in the years leading up to the coup and the role played by Church before and during the dictatorship. The foundation upon which was built this thesis was to sources the documentary collections of institutions that were part of the Church's project as well as the institution itself, the research object. Pillar master of the foundation built by sources rested on oral source made up of former teachers - the first of the institution - alumni and former students who became teachers of the faculty. The spatial area was the North Limoeiro city, with the specific focus the institution researched and time frame as the first ten years of creation of the faculty which converges with the ten hardest years of the dictatorship. The results found in the research, found that political practices developed between the Church and the Limoeirense elite, and the role of the institutions created by Don Aureliano Matos during the development of church design, reinforced the dictatorial politics in the micro-region of Baixo Jaguaribe ; the educational project developed in North Limoeiro under the auspices of the Church had close relations with the project civil-military government; policies and practices in higher education under the Church's control strengthened the conservative social order of the dictatorship in the micro, sometimes by the practices of purges and persecutions, and at other times through accommodation and reconciliation in daily practices. Ie the FAFIDAM kept the conservative order, which was the foundation of its construction,